Ultrasonic-assisted stewing enhances the aroma intensity of chicken broth: A perspective of the aroma-binding behavior of fat. (1st January 2023) - Qi, Jun; Jia, Chuan-kang; Zhang, Wen-wen; Yan, Hui-min; Cai, Qing-yuan; Yao, Xiu-ning; Xu, Kuo; Xu, Ying; Xu, Wen-ping; Xiong, Guo-yuan; Li, Mei-qi
Highlights: Ultrasonic-assisted stewing enhanced the aroma intensity of chicken broth. The level of odorants increased by 3-fold after 1 h of thermo-ultrasound. The volume fraction of oil droplets increased to 1% after thermo-ultrasound. Ultrasonic-assisted stewing could be used to prepare heat-stable emulsions. Abstract: This experiment investigated the underlying mechanism of ultrasonic-assisted stewing to enhance the aroma intensity of chicken broth by measuring fat content, oil droplet sizes, zeta potential, viscosity, surface protein loading, lipid oxidation, and aroma compound concentrations. As the thermo-ultrasound time increased, the fat content increased from 0.3 % to 1.2 %, resulting in a milky white appearance. After 1 h of thermo-ultrasound, the broth had the smallest particle size and the highest surface protein load, viscosity, and emulsion stability, as well as the highest total amount of aroma-active compounds of 314.70 ng/mg. With the further extension of thermo-ultrasound time, lipid oxidation increased, but the stability of chicken broth decreased, lowering the content of aroma-active compounds. These outcomes suggested that thermo-ultrasound could enhance the aroma intensity of chicken broth by increasing the fat content and the emulsion stability of the broth.